1

Extra differentiation problems with solutions.

These problems were prepared using Maple. There are sometimes 2 answers; the second is just Maple’s
“simplification” of the first answer. In most cases there are other reasonable ways of writing the answer.

1.
2.

3.
4.
5.

6.
7. 

d
−x2 + 4 x − 1 = −2 x + 4
dx 

d
4 x8 − 5 x3 − x2 + 11 = 32 x7 − 15 x2 − 2 x
dx 

d
1 + 4 x6
x−3 − 4 x3 = −3 x−4 − 12 x2 = −3
dx
x4 

d
1/3 x3 − 1/2 x2 + 3 x = x2 − x + 3
dx 

d
5 x−1 − 3 x−3 − 6 x−5 = −5 x−2 + 9 x−4 + 30 x−6
dx
d
dx

x + 3 x−1

x2 − 1 − x−1  

=

3 x5 + 2 x 3 + 3 x + 6
x3 

9 
10 
d  3
= 10 y 3 + 2 y 2 − 1 y (3 y + 4)
y + 2 y2 − 1
dy 

√ 

8. g(z) = 2 z 2 + 1
z−1 


2 z2 + 1
10 z 2 − 8 z 3/2 + 1

z − 1 + 1/2 √
g 0 (z) = 4 z
= 1/2
z
z 

4 2 
5
6
9. f (u) = u3 + 1
u + 3 (3 u − 2)   

4 2 
4 
4 2 
5
3
5
5
6
6
f 0 (u) = 12 u3 + 1
u2 + 3 (3 u − 2) u2 +10 u3 + 1
u + 3 (3 u − 2) u+18 u3 + 1
u + 3 (3 u − 2)
10.

d
dx 

3x − 2
2x + 7 

= 3 (2 x + 7)−1 − 2

11.

d
dx 

x2 − 1
x−4 

=

2 x (x − 4) − x2 + 1

12.

d
du 

u−4
u2 − 1 

=

u2 − 1 − 2 (u − 4) u

(x − 4)

3x − 2

(2 x + 7)2

2

2

(u2 − 1)

=

x2 − 8 x + 1
(x − 4)2

=−

t2 − 2 t + 2
t2 − 1  

(2 t − 2) t2 − 1 − 2 t2 − 2 t + 2 t

= 25 (2 x + 7)−2

u2 + 1 − 8 u
(u2 − 1)

2

13. f (t) =
f 0 (t) =

14.

d
dx

(t2 − 1)2 

1
(x − 1) (x − 2) 

=

3 − 2x
2

=2

(x − 1) (x − 2)

2

−3 t + t2 + 1
(t2 − 1)2

=−

2x − 3
2

(x − 1) (x − 2)

2

2
(x − 1) x2 − 3
x2 + 1 

!

x2 − 3 + 2 (x − 1) x

15.

d
dx

16.  

√ 
√ 
d
sin x2 − 2 = 2 cos x2 − 2 x
dx

17.

=  

cos 5 x2 x
d p
sin (5 x2 ) = 5 p
dx
sin (5 x2 ) 

x+1

x2 + 1 

(x + 1) x

1

18.

d
dx

19.

d
tan (5 x) = 5 (sec (5 x))2
dx

20.

=√

x2

+1

(x2

=−

3/2

+ 1)   

x2 + 1 − 2 (x − 1) x2 − 3 x
2

(x2 + 1)

=

x4 − 3 − 8 x + 6 x 2

x−1

(x2

+ 1)3/2  

2
d
cot x2 = −2 csc x2
x
dx 

cos (x)
x2 

sin (x) x + 2 cos (x)
− sin (x) x2 − 2 cos (x) x
=−
4
x
x3

21.

d
dx

22.

d
(cot (x) − 3 csc (5 x)) = − (csc (x))2 + 15 csc (5 x) cot (5 x)
dx

23.

d
dt

24.

−2 + (cos (2 x))2
d
3
2
(tan (2 x) sec (2 x)) = 2 (sec (2 x)) + 2 (tan (2 x)) sec (2 x) = −2
3
dx
(cos (2 x))

25.

26. 

=

cos (t)
1 − sin (t) 

=

sin (t) (−1 + sin (t)) + (cos (t))2
(−1 + sin (t))

2

−1 

4 4  

5 
d 
= 5 1/5 x5 − 3 x + x−2
x − 3 − 2 x−3
1/5 x5 − 3 x + x−2
dx
d
(y csc (5 y)) = csc (5 y) − 5 y csc (5 y) cot (5 y)
dy 

2/5
27. f (x) = x5 − 4 x + 1
5 x4 − 4
f 0 (x) = 2/5
3/5
(x5 − 4 x + 1)
28. 

d 
4
3
(cos (x)) = −4 (cos (x)) sin (x)
dx

29.



√ 2  tan ( x) (sec ( x))2
d 

tan x
=
dx
x

30.

= − (−1 + sin (t)) 

2 
2 
d 
sec u−1
− tan u−1
=0
du

(x2 + 1)

2

3
31. g(t) =

sin (3 t) + cos (3 t)
2

(cos (3 t)) + 1  

(3 cos (3 t) − 3 sin (3 t)) (cos (3 t))2 + 1 + 6 (sin (3 t) + cos (3 t)) cos (3 t) sin (3 t)
g 0 (t) =  

2
(cos (3 t))2 + 1

=3

sin (3 t) (cos (3 t))2 − sin (3 t) − (cos (3 t))3 + 3 cos (3 t)
4

2

(cos (3 t)) + 2 (cos (3 t)) + 1

Sign up to vote on this title
UsefulNot useful